Strategi Efektifitas Penganggaran Berbasis Kinerja Dalam Program Pengembangan Pemuda dan Olahraga Pada Dinas Pemuda dan Olahraga Kabupaten Seram Bagian Barat - Patty, Jafar; Rahawarin, Mohamad Arsad; Selanno, Hendry (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the effectiveness of performance-based budgeting in the Youth and Sports Office of West Seram Regency to support youth development programs and improve sports achievements. A quantitative approach was employed using the Analytical Hierarchy Process (AHP) method to determine priority strategies for budget management. Data were collected through interviews, observations, and documentation, involving 15 respondents from five pentahelix elements: government, academics, community, media, and development planning sectors. The findings reveal strong internal factors, such as organizational commitment, experienced human resources, and productive partnerships, which support the implementation of performance-based budgeting. Externally, government support, CSR opportunities, and technological advancements provide a favorable environment for aggressive budget optimization strategies. However, challenges such as limited HR capacity, dependence on regional budgets, and disaster risks must be addressed. The study recommends strengthening HR capacity through technical training and digital literacy, leveraging technology for transparent financial management, and diversifying funding sources via private partnerships and international grants. These strategies are expected to enhance the effectiveness, transparency, and accountability of regional financial management while delivering tangible impacts on youth development and sports performance.